Proposed Usability Heuristics for Testing Gestural Interaction - Chuan, N.K. (Institute of Electrical and Electronics Engineers Inc., 2015)
Heuristic evaluation is a fast and effective method of usability testing. However, usability heuristics framework used for general testing may not be suitable to evaluate gesture vocabulary of mainstream gestural interaction found in touchscreen devices or emerging technologies natural user interface that uses motion tracking. There is a need to do so during early stages of product development. The objective of this study is to create a set of gesture-specific heuristics that would complement existing general usability heuristics for design and testing of new gestural interaction. The method to do so is to review previous studies of gestural interaction design and usability testing. The result of the study is condensed set of four gesture-specific heuristics. Â© 2014 IEEE.